Poetry authored by vulnerable populations as secondary data: methodological approach and considerations. Issue 4 (1st October 2020) - Ellis, Taylor; Li, Qingyi; Bertram, Jessica M.; Meadows, James T.; Ozturk, Burcu; Nelson-Gardell, Debra
ABSTRACT: Staller (2015) presented the challenge to qualitative researchers of valuing data that already exists and using it as a starting point to explore "whether there are questions which can be asked and answered using that evidence" (p. 732) as opposed to the traditional approach of beginning with research questions. A class of social work doctoral students learning qualitative methods assumed this challenge using published poetry written by male youth adjudicated for their problematic sexual behaviors in a creative writing class hosted by the Alabama Writers' Forum in a secure facility in the southeastern United States. This article presents an innovative method of analyzing poetry written by a vulnerable population for non-research purposes as existing, secondary qualitative data. Situated within the field of arts-based research, we discuss secondary data in qualitative research, the process of developing and applying the method, as well as the ethical dilemmas that emerged in the process.